Factors contributing to employee retention in the case of component part department in Panasonic Appliances Refrigeration Devices Malaysia Sdn. Bhd / Ain Munirah Azmi - Azmi, Ain Munirah (Faculty of Business and Management, 2017)
The purpose of this paper is to investigate and study the factors contributing to Employee Retention in the case of Component Part department in Panasonic Appliances Refrigeration Devices Malaysia Sdn. Bhd. In this study, the researcher chooses to use three independent variables which working environment, rewards and work-life policies and its relation to dependent variable which is employee retention. A survey questionnaire will be distributed to 86 employees as a sample size. This research will use simple random sampling technique. The quantitative data in this research was analyzed by descriptive statistics using Statistical Package for the Social Sciences Software (SPSS). As a conclusion, this research helps the other researcher to explore the factor contributing to employee retention.